Beth Levine’s Legacy: From the Discovery of BECN1 to Therapies. A Mentees’ Perspective - An, Zhenyi; Chiang, Wei-Chung; Fernández, Álvaro F.; Franco, Luis H.; He, CongCong; Huang, Shu-Yi; Lee, Eunmyong; Liu, Yang; Sebti, Salwa; Shoji-Kawata, Sanae; Sirasanagandla, Shyam; Wang, Richard C.; et al. (Frontiers in Cell and Developmental Biology, 2022)
With great sadness, the scientific community received the news of the loss of Beth Levine on June 15th, 2020. Dr. Levine was a pioneer in the autophagy field and work in her lab led not only to a better understanding of the molecular mechanisms regulating the pathway, but also its implications in multiple physiological and pathological conditions, including its role in development, host defense, tumorigenesis, aging or metabolism. This review does not aim to provide a comprehensive view of autophagy, but rather an outline of some of the discoveries made by the group of Beth Levine, from the perspective of some of her own mentees, hoping to honor her legacy in science.